2021
DOI: 10.3390/jcm10071526
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation for Fulminant Myocarditis: Increase of Cardiac Enzyme and SOFA Score Is Associated with High Mortality

Abstract: We aimed to evaluate the outcomes of patients with fulminant myocarditis and investigate the factors associated with mortality. This is a retrospective single-center cohort study that included adult and pediatric patients with fulminant myocarditis treated at Samsung Medical Center between September 2004 and December 2019. The primary outcome was in-hospital mortality. Among 100 patients, 71 underwent veno-arterial extracorporeal membrane oxygenation (ECMO) (ECMO group). Comorbidities were not significantly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The most important clinical predictor is the prolonged prevalence of arrhythmias be they atrioventricular block or ventricular arrhythmias [27]. SOFA score has also been associated with the patient outcome with scores >12 shown to be predictive of death or established heart failure [28]. CK-MB is the most well-reported biomarker with two independent studies agreeing to its prognostic value with levels >95 ng/mL [28] or > 185 IU/L [27] predicting a lower chance of successful weaning.…”
Section: The Role Of Extracorporeal Membrane Oxygenation In the Manag...mentioning
confidence: 99%
“…The most important clinical predictor is the prolonged prevalence of arrhythmias be they atrioventricular block or ventricular arrhythmias [27]. SOFA score has also been associated with the patient outcome with scores >12 shown to be predictive of death or established heart failure [28]. CK-MB is the most well-reported biomarker with two independent studies agreeing to its prognostic value with levels >95 ng/mL [28] or > 185 IU/L [27] predicting a lower chance of successful weaning.…”
Section: The Role Of Extracorporeal Membrane Oxygenation In the Manag...mentioning
confidence: 99%
“…These studies are summarized in Table 2. Most recently, Lee et al [60] analyzed risk factors in pediatric patients diagnosed with fulminant myocarditis treated with VA-ECMO. They showed that among 71 patients who underwent ECMO, use of creatinine kinase-MB (CK-MB) with a cut-off of 94.74 ng/mL and a SOFA score with a cut-off score of 12 accurately predicted mortality.…”
Section: Initial Supportmentioning
confidence: 99%
“…6 Venoarterial extracorporeal membrane oxygenation (VA-ECMO) has been proven to be an effective support method for AFM with cardiogenic shock. 6 Many studies have identified prognostic factors and risk factors for fulminant myocarditis supported by ECMO. [6][7][8][9] The additional use of renal replacement therapy (RRT) or mechanical ventilation during ECMO is a common strategy for preventing kidney dysfunction, fluid and electrolyte imbalance and promoting recovery.…”
Section: Introductionmentioning
confidence: 99%
“…6 Many studies have identified prognostic factors and risk factors for fulminant myocarditis supported by ECMO. [6][7][8][9] The additional use of renal replacement therapy (RRT) or mechanical ventilation during ECMO is a common strategy for preventing kidney dysfunction, fluid and electrolyte imbalance and promoting recovery. However, it is unclear if RRT use during ECMO support and different ventilator settings in positive end-expiratory pressure (PEEP) influence mortality in adult patients with AFM receiving ECMO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation